Claims-based measures of prescription opioid utilization: A practical guide for researchers. (1st November 2021) - Heins, Sara E.; Buttorff, Christine; Armstrong, Courtney; Pacula, Rosalie Liccardo
Abstract: Background: Given the increased attention to the opioid epidemic and the role of inappropriate prescribing, there has been a marked increase in the number of studies using claims data to study opioid use and policies designed to curb misuse. Our objective is to review the medical literature for recent studies that use claims data to construct opioid use measures and to develop a guide for researchers using these measures. Methods: We searched for articles relating to opioid use measured in health insurance claims data using a defined set of search terms for the years 2014–2020. Original research articles based in the United States that used claims-based measures of opioid utilization were included and information on the study population and measures of any opioid use, quantity of opioid use, new opioid use, chronic opioid use, multiple providers, and overlapping prescriptions was abstracted. Results: A total of 164 articles met inclusion criteria. Any opioid use was the most commonly included measure, defined by 85 studies. This was followed by quantity of opioids (68 studies), chronic opioid use (53 studies), overlapping prescriptions (28 studies), and multiple providers (8 studies). Each measure contained multiple, distinct definitions with considerable variation in how each was operationalized. Conclusions: Claims-based opioid utilization measures are commonly used in research, but definitions vary significantly from study to study. Researchers should carefully consider which opioid utilization measures and definitions are most appropriate for their study and recognize how different definitions may influence study results. Highlights: Many use claims data to study opioid prescribing trends or evaluate policies. Studies use diverse and conflicting measures of prescription opioid utilization. Inconsistent use of measures makes cross-study comparisons challenging. Careful selection of appropriate opioid utilization measures is needed.